EP.TH.494Preclinical feasibility of in situ isolated normothermic liver chemoperfusion. (28th October 2021) - Clark, Tamsyn; Ebeling, Georg; Voyce, Daniel; Bau, Luca; Coussios, Constantin; Friend, Peter
Abstract: Aims: Up to 85% of patients with liver metastases have inoperable hepatic tumour burden. Isolated liver perfusion involves vascular isolation of the liver in situ and regional delivery of chemotherapy, avoiding dose-limiting extra-hepatic toxicity. In this series, we develop a surgical protocol to demonstrate the feasibility of isolated normothermic liver perfusion (INLP) and investigate short-term safety and feasibility of delivering high-dose chemotherapy. Methods: Laparotomy and complete, vascular isolation of the liver was performed on 55-65Kg pigs (n = 6). The hepatic artery (HA), portal vein (PV) and inferior vena cava were cannulated and liver NMP established. Veno-venous bypass maintained systemic circulation. High-dose doxorubicin was administered to the isolated liver, circulated for 1 hour and vascular reconnection performed. Physiological parameters were measured and doxorubicin quantified in blood, bile and tissue by high-performance liquid chromatography. Results: INLP with doxorubicin delivery achieved physiological flow rates (PV 0.7L/min (0.6-0.9L/min); HA 0.3L/min (0.2-0.4L/min)) and pH (median 7.3 (7.24-7.38)), with a median lactate of 0.42mmol/L. Median peak AST and ALT were 1045 U/L and 47 U/L respectively. Doxorubicin decay was fitted with a 2-compartmental model; distribution half-life was 1.9 minutes and plasma Cmax was higher than if given systemically resulting in mean hepatic tissue levels of 26+/-11.6 µg/g. There was no leak during INLP and doxorubicin was undetectable in kidney or heart. Conclusions: Surgical isolation and NMP of the liver in situ, with concurrent veno-venous bypass is feasible and enables high-dose drug delivery resulting in therapeutic tissue levels with no off-target toxicity. Further safety studies are required.